Eicosapentaenoic and docosahexaenoic acids attenuate methotrexate-induced apoptosis and suppression of splenic T, B-Lymphocytes and macrophages with modulation of expression of CD3, CD20 and CD68. (October 2021) - Elsayed, Hassan Reda Hassan; Anbar, Hanan S.; Rabei, Mohammed R.; Adel, Mohamed; El-Gamal, Randa
Highlights: Methotrexate (MTX), a commonly used chemotherapeutic agent causes multi-organ damage e.g. suppression of splenic lymphocytes and macrophages. Eicosapentaenoic and Docosahexaenoic (EPA & DHA) Omega-3 Fatty Acids could exhibit a protective potential against MTX-induced splenic injury. EPA+DHA could restoration macrophages, B- and T-lymphocytes as seen through studying the expression of CD68, CD20 and CD3 respectively. The mechanisms underlying the protective role of EPA+DHA may be antioxidant, anti-inflammatory, and anti-apoptotic. EPA +DHA can be used as an adjuvant therapy to MTX to support its action as well as preventing its adverse effects on different tissues e.g. spleen. Abstract: Methotrexate (MTX) is a chemotherapeutic agent used for cancer and autoimmune disorders. MTX may cause multi-organ affections. However, few studies examined MTX-induced splenic suppression and therapeutic modalities against it. This is the first study to explore the efficacy of omega-3 fatty acids; Eicosapentaenoic (EPA) and Docosahexaenoic (DHA) against MTX-induced splenic suppression and its effect on splenic macrophages and lymphocytes. Five groups of Sprague Dawley rats were used. Group 1 received saline; group 2: omega-3 only; group 3: a single dose of MTX (20 mg/kg); groups 4 and 5: MTX (20 mg/kg) + either omega-3 (150) or (300 mg/kg) once daily, respectively, given for two days before MTX and three days after it. Splenic tissues were then removed, evaluated for oxidative stress markers; GSH, MDA, and for mRNA expression of the apoptotic marker caspase-3, the anti-apoptotic marker Bcl-2 and the inflammatory cytokine TNFα. Moreover, H&E stain, Prussian blue stain for iron, and immunohistochemical staining for TNFα, T lymphocyte marker; CD3, B lymphocyte marker; CD20, and macrophage marker; CD68, were performed with morphometric analysis. EPA and DHA could decrease the MTX-induced increase in the histopathological injury score, splenic hemosiderin, splenic MDA, mRNA expression of TNFα, caspase-3 and could increase the MTX-induced decrease in Splenic GSH and mRNA expression for Bcl-2. It also decreased the MTX-induced elevation in the immunopositive area of TNFα, and increased the area percentage of CD3+, CD20+ and CD68+ cells. Therefore, omega-3 can be a promising adjuvant to help MTX action with prevention of its deleterious effects on spleen.